The News Processing of Al-Aqsa Flood on Arabic News Websites: A Comparative Analytical Study of Al Jazeera and Al Arabiya Websites - Nejadat, Ali; A. Abu Shhadeh, Esraa (Arts and Social Sciences Series, 2026)
Abstract: The study aimed to monitor and analyze how the website of Al Jazeera and Al Arabiya channels deals with the events of the Al Aqsa flood, by identifying the topics covered by the two sites, and relied on the content analysis approach, using the analysis form as a tool to obtain information,The study found that the Al Jazeera and Al Arabiya websites are interested in military and security topics and issues in the first place, by (41.8%) and (48.5%) of each, respectively, compared to the rest of the various topics and issues of the Al Aqsa flood. The results also showed that the Gaza area ranked first among the geographical areas included in the topics that dealt with the events of the Al-Aqsa flood, with a percentage of (86.7%) in the location of Al-Jazeera, and (30.2%) in the location of Al-Arabiya. The study recommends the need to pay attention to the explanatory and analytical coverage of the issues of wars and conflicts, as well as the need to give the scope of the West Bank, east Jerusalem and the territories (48) more attention as no less violated and besieged areas. Keywords: News Processing, Al Jazeera Website, Al Arabiya Website, Al-Aqsa Flood, War on Gaza.